The Economics of Abortion Policy - Damian Clarke (Institute of Labor Economics (IZA), 2023)
This article provides a review of the economics of abortion policy. In particular, it focuses on the determinants of abortion reform, as well as the effects of abortion reform on individual circumstances. The economic literature on abortion policy is broad, studying abortion reforms that have occurred over the past two centuries, although there is a concentration of studies examining policy reform over the 20th and 21st centuries. The literature has examined a range of policies: both those which restrict access and those which legalise elective abortion, but within these two broad classes, the precise nature of policy reform can vary greatly. Policy reforms studied range from particular types of limits or financial barriers restricting access for particular age groups, up to policies which entirely criminalise or legalise elective abortion. The economic literature on abortion reform has illuminated a number of clear links, showing that increased availability of abortion decreases rates of undesired births, and vice versa when access to abortion is limited. These effects have been shown to have downstream impacts in many domains such as family formation, educational attainment, labour market attachment, as well as impacts on health, empowerment and well-being. There is mixed evidence when examining the impact which abortion reform has on cohorts of children exposed to reform variation. Much of what is known in the economic literature on abortion is gleaned from country-level case studies and cohort variation in access, with this evidence generated from a relatively small number of countries in which reforms have occurred and data is available. In general, much of the literature available covers low fertility and industralised settings. Additional evidence from other settings would allow for a more broad understanding of how abortion reform affects well-being.
Keywords: A33; I18; J10; K36; O57; 330; abortion; contraceptives; labour markets; fertility; child outcomes; crime; health; political economy